Risk Assessment of Chlorothalonil as a Probable Human Carcinogen on Selected Vegetables in an Eastern China Province - Sun, Chen-Xi; Liu, Bing; Wang, Wen-Bo; Yuan, Xue-Xia; Wu, Yuan-Juan (Frontiers in Public Health, 2022)
Objectives: This study aimed to provide an assessment of chlorothalonil’s possible carcinogenic risk posed to the public. In combination and comparison with the non-carcinogenic risk, the results hopefully could provide useful insights, early warning and reference for policy formulation. Methods: This study firstly investigated the occurrence of chlorothalonil on selected key vegetables for different scenarios, then conducted an exposure assessment with officially published data. Lastly, both the non-carcinogenic and carcinogenic risk of chlorothalonil were calculated using Monte-Carlo simulation. Results: Even though mean non-carcinogenic risks of chlorothalonil for all scenarios were below threshold value, the mean carcinogenic risks for maximum-risk scenario and most-likely-risk scenario were mostly above threshold value. High probabilities of exceedance of threshold value existed for carcinogenic risk under all scenarios. Conclusion: Potential threat to public health existed for conventionally ‘safe’ pesticide if considering the possible carcinogenicity. Extra caution should be taken and the potential carcinogenic effects should be included into consideration for better protection of public health during the policy formulation process.